Effect of dried sewage sludge on compressive strength of concrete - A. L., Amminudin; Putra Jaya, Ramadhansyah; Doh, Shu Ing; S. A., Mangi; W. I., Mohd Haziman (2019)
Sewage sludge is a waste product generated from the wastewater treatment process at the treatment plant. The amount of sewage sludge produced is increases every year as the population increased. Poor management of sewage sludge will give negative impact to the environment. Replacing cement with sewage sludge ash is more significant to reduce the amount of waste material from sewage treatment plants. In this study, the various percentage of dried sewage sludge (DSS) has been added to replace the cement. Sewage sludge was dried in the oven with 100°C for 24 hours, then sieve through the sieve size 300 μm. Then, DSS was used in the concrete instead of cement with the replacement percentage of 0%, 5%, 10%, and 15% by weight. The compressive strength of concrete cube specimens was investigated after 7 and 28 days of curing. The results showed that the compressive strength of concrete specimens increased with the replacement of cement in concrete with 5 % to 10 % DSS, but the achieved maximum strength still lower compared to the control sample. However, the compressive strength of concrete specimens decreased when the DSS replacement of cement is more than 10 % by weight. The result of XRF test also showed that DSS has good potential to replace cement in concrete.